2013
DOI: 10.1097/nnd.0b013e318291c0cc
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reflective Practice Education on Self-Reflection, Insight, and Reflective Thinking Among Experienced Nurses

Abstract: A mixed-method study was conducted to determine whether nurses' participation in a reflective practice continuing education program using a structured reflection model makes a difference in nurses' self-reflection, insight, and reflective thinking about clinical practice situations. Findings suggested that use of structured reflection using question cues, written narratives, and peer-facilitated reflection increased nurses' engagement in self-reflection and enhanced reflective thinking in practice. Including r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 0 publications
1
46
0
2
Order By: Relevance
“…When using narratives to enhance reflective practice in nursing, the process of thinking back on a past experience to obtain new understanding was assumed by most of the authors as the theoretical starting point for engaging in the process (Hewitt, ; Asselin & Fain, ; Correia & Santiago, ; Forneris & Peden‐McAlpine, ; Levett‐Jones, ; Hargreaves, ; Taylor, ; Kim, ; Durgahee, ; Maeve, ). Indeed, this way of conducting reflection allowed participants to hold themselves apart and look back on what had happened in the clinical situation, to gain new insight into themselves and their practice (Asselin & Fain, ; Hewitt, ; Maeve, ; Taylor, ). Accordingly, many articles focused on defining how this way of examining practice was crucial when researchers were looking for ways to promote knowledge development and gain additional learning from experiences in nursing practice (Cathcart & Greenspan, ; Correia & Santiago, ; Durgahee, ; Forneris & Peden‐McAlpine, ; Hargraves, 2004; Kim, ; Levett‐Jones, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…When using narratives to enhance reflective practice in nursing, the process of thinking back on a past experience to obtain new understanding was assumed by most of the authors as the theoretical starting point for engaging in the process (Hewitt, ; Asselin & Fain, ; Correia & Santiago, ; Forneris & Peden‐McAlpine, ; Levett‐Jones, ; Hargreaves, ; Taylor, ; Kim, ; Durgahee, ; Maeve, ). Indeed, this way of conducting reflection allowed participants to hold themselves apart and look back on what had happened in the clinical situation, to gain new insight into themselves and their practice (Asselin & Fain, ; Hewitt, ; Maeve, ; Taylor, ). Accordingly, many articles focused on defining how this way of examining practice was crucial when researchers were looking for ways to promote knowledge development and gain additional learning from experiences in nursing practice (Cathcart & Greenspan, ; Correia & Santiago, ; Durgahee, ; Forneris & Peden‐McAlpine, ; Hargraves, 2004; Kim, ; Levett‐Jones, ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, from this point of view, using narratives as a tool for assessing practice emerged as an opportunity for learning from practice (Asselin & Fain, ; Hargreaves, ; Levett‐Jones, ). In this sense, although there were some discrepancies in how to conduct assessments – the kind of narratives subject to evaluation (Hargreaves, ), or the potential tension between reflection and assessment (Levett‐Jones, ) – authors finally suggested that integrating this approach properly into nurses’ practice might contribute to the process of learning and knowledge development.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has shown that structured reflection models enhance reflective thinking in clinical 2 practice (Asselin & Fain, 2013) and that students' narratives may uncover practices that otherwise might go unnoticed (Levett-Jones, 2007). Schön (1995) described two types of reflection; "reflection-in-action" and "reflection-on-action".…”
Section: Introductionmentioning
confidence: 99%